PERFORMANSI WAVELENGTH DIVISION MULTIPLEXING PADA JARINGAN OPTIK - Dewa Gede Agung Mahesa Yoga; Sheena Graceline; Rizky Imanuel S; Pande Ketut Sudiarta; I Gusti Agung Komang Diafari Djuni Harta (Program Studi Teknik Elektro UNUD, 2023)
The process of sending information is currently needed to be fast and efficient. One of the solutions to meet the needs of fast information is to use transmission via a Wavelength Division Multiplexing (WDM) network. The purpose of this study is to determine and analyze the performance of WDM networks and the impact that occurs when EDFA is added and its use in PON networks. This research will utilize optisystem 7.0 software in carrying out design simulations and finding out the results of receiver power, q-factor, and BER which will then be used as a comparison in this study. The results of the analysis provide evidence that the use of WDM in the delivery process is more efficient because it can transmit several wavelengths at a time, but will have a negative effect on distance, but this can be overcome by using EDFA in WDM networks. The use of WDM-PON will expand the scope of the process of sending information. The results of this study can prove the performance in the use of WDM. In the future, it is necessary to carry out further research by adding other comparison parameters so that the results obtained will be more certain. As well as the use of the latest version of the optisystem application will help and facilitate the process of collecting information and data.